(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study investigates the morphological changes and later movement of the Ramganga River from 1923–2014 based on remotely sensed data and topographic maps. It focused on the Rohilakhand Plain in the Western Gangetic Plain (WGP), India, where channel shift is common. This study utilized Landstat-MSS images from 1972–2014 and georeferenced the Topographical Sheet (NG 44–2) from the US Army Map Service, 1923. Various morphological parameters, such as channel width, sinuosity, braiding intensity, active channel area, and channel bar area, are used to monitor the lateral movement of the river. The result reveals the complex hydrodynamic mechanisms of the river, which include an increasing tendency for braiding, decrease in active channel width and length, increase in the number of cut-offs and channel avulsions, alternating eastward and westward migration, and alternating stages of increasing and decreasing sinuosity.